Pharmacogenomic Study of Selected Genes Affecting Amlodipine Blood Pressure Response in Patients with Hypertension - Jan A; Alanzi AR; Mothana RA; Kaimori JY; Ali SS; Muhammad T; Saeed M; Akbar R; Khan M (Dove Medical Press, 2024)
Asif Jan,1,2 Abdullah R Alanzi,3 Ramzi A Mothana,3 Jun-Ya Kaimori,4 Syed Shaukat Ali,5 Tahir Muhammad,6,7 Muhammad Saeed,8 Rani Akbar,9 Mehtab Khan10 1Department of Pharmacy, University of Peshawar, Peshawar, 25000, Pakistan; 2District Headquarter Hospital (DHQH) Charsadda, Charsadda, 24430, Pakistan; 3Department of Pharmacognosy, College of Pharmacy, King Saud University, Riyadh, 1151, Saudi Arabia; 4Department of Nephrology, Osaka University Graduate School of Medicine, Osaka, 565-0871, Japan; 5Department of Pharmacy, University of Malakand, Malakand, Pakistan; 6Molecular Neuropsychiatry & Development (Mind) Lab, Campbell Family Mental Health Research Institute, Centre for Addiction and Mental Health, Toronto, ON, 43964, Canada; 7Institute of Medical Science, University of Toronto, Toronto, ON, 43964, Canada; 8Department of Pharmacy, Qurtaba University of Science and Technology, Peshawar, 25000, Pakistan; 9Department of Pharmacy, Abdul Wali Khan University Mardan, Mardan, 23200, Pakistan; 10Department of Biology, Faculty of Science, University of Moncton, Moncton, NB, E1A 3E9, CanadaCorrespondence: Asif Jan, Email asif.research1@gmail.comIntroduction: Despite the availability of various antihypertensive medications, the response to these medications varies among individuals. Understanding how individual genetic variations affect drugs treatment outcomes is a key area of focus in precision medicine. This study investigated the correlation between single nucleotide polymorphisms (SNPs) in selected genes (CACNA1C, CACNA1D, ABCB1, ACE, ADBR2, and NOS1AP) and the blood pressure (BP) control by amlodipine.Methods: Four hundred individuals of Pashtun ethnicity undergoing amlodipine treatment for hypertension were included in the present study and divided into the controlled (BP less than 140/90 mmHg) and uncontrolled (BP greater than 140/90 mmHg) hypertension groups. Blood samples (3 mL) were collected from each participant, and DNA was extracted using the Kit method. Ten SNPs in amlodipine pharmacogenes were selected and genotyped using real-time PCR with the TaqMan® system. Logistic regression model was used to determine the association between SNPs and the amlodipine BP response.Results: Notable association were observed between SNP rs2239050/CACNA1C and amlodipine blood pressure response, with GG genotype carriers demonstrating a better response (P=0.004) than individuals carrying CC or CG genotypes. SNP rs312481/CACNA1D also exhibited a positive pharmacogenetic association, Individuals with the GG genotype showing a considerable reduction in BP (P=0.021) compared to participants with AA or GA genotypes. In case of SNP rs429/ACE individuals carrying TA genotype were less likely to achieve BP control (P=0.002) than AA genotype carriers.Conclusion: Our finding suggests that the SNPs rs2239050/CACNA1C, rs312481/CACNA1D and rs429/ACE influence amlodipine blood pressure response in patients with hypertension. It is recommended that prior knowledge of amlodipine associated pharmacogenetic variants is important that could improve its treatment outcomes in hypertensive patients.Keywords: pharmacogenomics, hypertension, genetic markers, personalized medicine, amlodipine, Pashtun, Pakistan